2014
DOI: 10.1080/03079457.2014.967176
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis ofGallibacterium anatisin a natural infection model fulfils Koch’s postulates: 2. Epididymitis and decreased semen quality are the predominant effects in specific pathogen free cockerels

Abstract: Pathogenesis of Gallibacterium anatis was investigated in specific pathogen free cockerels. Birds aged 35 weeks were infected intranasally with G. anatis whereas negative controls were left uninfected. Following infection, necropsy, bacteriological and histopathological investigations were performed in birds killed at 3, 7, 10, 28 and 38 days post infection (d.p.i.). Additionally, semen samples were collected twice a week until 5 weeks post infection for quality assessment. No clinical signs and gross patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…anatis has been noted in four-day-old poultry birds by quantitative PCR (qPCR) (Huangfu et al 2012) and also been isolated from the egg yolks and ovarian follicles of adult hens ten days after intranasal inoculation, supporting the vertical transmission hypothesis (Kohlert 1968;Janetschke & Risk 1970;Shapiro et al 2013;. G. anatis causes epididymitis and affects semen quality, consistent with the presumed venereal transmission (Paudel, Liebhart, Aurich, et al 2014). In natural cases, reproductive tract organs are affected mostly through ascending infections Neubauer et al 2009).…”
Section: Transmissionmentioning
confidence: 72%
See 3 more Smart Citations
“…anatis has been noted in four-day-old poultry birds by quantitative PCR (qPCR) (Huangfu et al 2012) and also been isolated from the egg yolks and ovarian follicles of adult hens ten days after intranasal inoculation, supporting the vertical transmission hypothesis (Kohlert 1968;Janetschke & Risk 1970;Shapiro et al 2013;. G. anatis causes epididymitis and affects semen quality, consistent with the presumed venereal transmission (Paudel, Liebhart, Aurich, et al 2014). In natural cases, reproductive tract organs are affected mostly through ascending infections Neubauer et al 2009).…”
Section: Transmissionmentioning
confidence: 72%
“…Gallibacterium have been reported across the world, such as European countries including Switzerland, Denmark, Germany, Norway, England, Sweden, Czech Republic and Austria (Mr az et al 1976;Bisgaard 1977;Mirle et al 1991;Neubauer et al 2009;Jones et al 2013); African countries like Nigeria, Egypt, Morocco (Addo & Mohan 1985;Elbestawy et al 2018;Nassik et al 2019); Asian countries including China, Taiwan, Iran, Syria, India and Japan (Suzuki et al 1996;Guo 2011;Huangfu et al 2012;Ataei et al 2017;Zhang et al 2017;Singh et al 2018); American countries such as the USA, Canada, Colombia, Peru and Mexico (Hacking & Pettit 1974;Shaw et al 1990;Bojesen et al 2008;Mendoza et al 2014;Paudel, Liebhart, Aurich, et al 2014;Ch avez et al 2017); and Australia (Jordan et al 2005). G. anatis, particularly biovar hemolytica, has recently gained importance due to its ability to cause both respiratory and reproductive infections, and its occurrence in countries on various continents including Europe, Asia, America, and Africa (Neubauer et al 2009).…”
Section: Epidemiology Prevalence and Host Rangementioning
confidence: 99%
See 2 more Smart Citations
“…This research indicated that the intranasal route of infection was very suitable to mimic the clinical situation. Based on this study, two further separate experimental trials in mature SPF chickens, hens and cockerels, were performed (Paudel et al ., 2014 a , 2014 b ). Macroscopic and microscopic lesions in the reproductive tract were successfully induced and the infection resulted in a drop in egg production due to severe folliculitis in addition to egg peritonitis.…”
Section: Introductionmentioning
confidence: 99%